Chip serration frequency-the primary cause of chatter during end milling operation - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Azhari, Marian; Farahain, S (2009)
Chatter is an unwanted but sometimes unavoidable phenomenon in machining. The term defines the self-excited violent relative dynamic motion between the cutting tool and work-piece. Chatter is undesirable due to its adverse effects on the product quality, operation cost, machining accuracy, tool life, machine-tool bearings, and machine-tool life. It is also responsible for reducing output. This paper includes the findings of an experimental study on instabilities of the chip formation process during end milling of Ti6Al4V alloy at different cutting conditions with two different two holders and its influencing factors on chatter formation. The instabilities of chip formation process are expressed as primary or secondary serrated frequency. The chip formed at different cutting conditions is analyzed and its frequency was calculated. It is observed that the primary serrated frequency is more prominent in end milling of Ti6Al4V alloy and its chip serration frequency has significant interaction effect with the with the prominent natural mode frequency of the system components. The vibration signals in frequency domain (FFT) have been analyzed to identify the chatter frequencies which have been compared with the chip serration frequencies in different cutting conditions for two different tool holders. It has been fairly concluded from the experimental findings that chatter is the outcome of resonance, in between the frequency of primary or secondary serrated frequency with the ‘prominent natural frequency’ modes of the system components.